Global Issue Pandemic and Technology Business: What The Role of Financing MSMEs an Islamic Perspective Theory? - Ridwansyah, Ridwansyah; Razimi, Mohd Syahril Ahmad; Suprianingsih, Okta; Amrina, Dania Hellin; Sisdianto, Ersi (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2025)
Purpose: This research aims to analyze the impact of the global pandemic on the operations, sustainability, and growth of Micro, Small, and Medium Enterprises (MSMEs) and examine the role of MSME financing from the perspective of Islamic economic theory as an instrument to support the recovery and sustainability of MSME businesses during the pandemic.Design/methodology: This research employs a qualitative approach to explore the impact of the global pandemic on micro, small, and medium enterprises (MSMEs) and the role of technology and Islamic financing. The study involves 15 MSME owners and managers, utilizing semi-structured interviews and focus group discussions for data collection.Findings The research found that the global pandemic caused a significant decline in MSME revenues and activities, especially in Bandar Lampung City and West Lampung Regency with a 30-40 percent decline. Key factors include decreased demand, supply chain disruptions and social restrictions. While some MSMEs are turning to digital technology to adapt, many rely on self-financing rather than bank loans. Islamic finance principles have the potential to support the recovery of MSMEs, but the low utilization of Islamic financing points to the need to improve Islamic finance literacy and accessibility.Practical Implications: Based on the finding that MSMEs that quickly adopt digital technologies are able to survive better during the pandemic, the government and relevant agencies should develop more widespread and affordable digital literacy programs. These programs should be designed to improve the technological skills of MSME players, including the use of e-commerce, digital marketing and digital financial platforms. This will help MSMEs to be more competitive and flexible in the face of market changes.Originality/Value: This research is unique because it combines an Islamic perspective, particularly in Islamic financing, with an analysis of business technology in the midst of a global crisis such as the pandemic